Balanced Anesthesia with Paravertebral Brachial Plexus Block in Maned Sloth (Bradypus torquatus) - Barbosa, Vivian Fernanda; Rossi de Almeida, Nádia; Dórea Neto, Francisco de Assis; Castro de Azevedo, Milena; de Jesus Moraes, Vinícius; Satyro Xavier de Oliveira, Vinícius (Acta Scientiae Veterinariae, 2024)
Background: Maned sloths are docile mammals endemic to the Brazilian Atlantic Forest, threatened with extinction due to the degradation of their habitat. Injury involving limbs is common when animals enter the urban environment. However, information regarding anesthesia in sloths is still scarce. This case is intended to report the anesthetic management of a maned three-toed sloth adult female undergoing amputation of the forelimb. Case: A female maned three-toed sloth weighing 4.2 kg with a history of burns to the thoracic forearm caused by electric shock was admitted by the University Veterinary Hospital. Ketamine (6 mg/kg - IM) and midazolam (0.2 mg/kg - IM) were administered as premedication, and after 10 min, tramadol (2 mg/kg - IV) was used. After detecting good general condition, the animal was referred to the surgical center for forearm amputation. Anesthetic induction was performed using isoflurane 2.5% (FiO2 = 1.0) via a mask, followed by intubation and maintenance using the same drug (1.5%). Next, the vertebrae C7 to C10 and T1 to T2 were identified, corresponding to the 7th, 8th, 9th, and 10th cervical medullary segments and the 1st and 2nd thoracic medullary segments, corresponding to the respective related spinal nerves, which give rise to the brachial plexus in the species. The vertebral foramen was accessed using a hypodermic needle inserted cranially and caudally to the transverse processes of C7, C8, C9, and C10 at a distance of 1 cm, laterally to the right of the animal’s dorsal midline at a 45º angle to the vertebral column. The 1st rib palpated dorsally allowed T1 and T2 to be located, and the needle was inserted according to the delimitations already described. The brachial plexus was blocked with 0.5 mL of lidocaine solution (1.5%) into each intervertebral foramen. After 10 min, the animal underwent thoracic limb amputation. Heart rate (HR), respiratory rate (f), end-tidal carbon dioxide (EtCO2), peripheral oxyhemoglobin saturation (SpO2), and rectal temperature (RT) were registered using a multiparametric monitor. The parameters recorded throughout the 50-min interval of the surgical procedure remained within the regular pattern of species. End-tidal isoflurane (EtISO) registered were 1.03 ± 0.19 mmHg. No movements were observed responding to pain stimuli, and the animal exhibited smooth recovery in 28 min. Discussion: Although limb trauma is a frequently reported condition, this study is a pioneer in the approach of using paravertebral brachial plexus block as part of the anesthetic protocol in sloths. Initially, a ketamine-midazolam combination was used to immobilize the animal for handling and preoperative clinical assessments. This combination of dissociative anesthetics with muscle relaxants has been widely used in anteaters and sloths, with physiological stability and smooth recovery reported. As thoracic limb amputation is a painful procedure, tramadol was used as an analgesic. Isoflurane was used for anesthesia maintenance, as reported in other studies with sloths. Brachial block using cervicothoracic access to the nerve roots that give rise to the brachial plexus was considered easy to perform. Lidocaine with vasoconstrictor was chosen based on the duration of the surgical procedure. Maintaining the sloth in a mild anesthetic plane associated with low isoflurane intraoperative requirement demonstrated the analgesic effectiveness of the locoregional block. The proposed anesthetic protocol was effective and safe, evidenced by stable physiological variables, no pain-related movements during surgery, and gentle animal awakening. Keywords: xenarthra anesthesia, ketamine, isoflurane, locoregional anesthesia.